2017
DOI: 10.5455/javar.2017.d224
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal helminths of sheep in Sherpur, Bangladesh

Abstract: Objective: Gastrointestinal (GI) parasitic infection is a prime cause of failures in sheep production. This study was conducted to ascertain the prevalence of gastrointestinal (GIT) helminths of sheep in Sherpur district, Bangladesh. Besides, prevalence of helminthiasis in sheep also assessed considering age, sex, nutritional condition and rearing system. Materials and methods: In total, 106 rectal fecal samples of sheep were randomly collected and were examined for the presence of ova by using direct smear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 14 publications
5
20
2
2
Order By: Relevance
“…There were no statistically significant differences in the shedding of nematode eggs between male and female sheep ( Table 2 ). These results are in agreement with the findings of a study from Ethiopia [ 31 ] and Bangladesh [ 32 ]. In contrast, a significantly higher number of female than male goats had nematode eggs in their faeces.…”
Section: Discussionsupporting
confidence: 93%
“…There were no statistically significant differences in the shedding of nematode eggs between male and female sheep ( Table 2 ). These results are in agreement with the findings of a study from Ethiopia [ 31 ] and Bangladesh [ 32 ]. In contrast, a significantly higher number of female than male goats had nematode eggs in their faeces.…”
Section: Discussionsupporting
confidence: 93%
“…Nematodes were recorded to be of highest prevalence (62.37%) followed by trematodes (56.02%) and cestodes (47.63%) (Table 1 and Figure 1). Similar findings were reported by Gupta et al, in 2013;Poddar et al, Islam et al, Ahmed et al, Sanalkumar et al, and Sohail et al, in 2017 and in 2018 by Jena et al, The higher prevalence of gastrointestinal parasites in tropical, subtropical and also temperate climates could be attributed to their wide range of adaptability (Soulsby, 1966;Sanyal, 1998 andPoddar et al, 2017). Rainy season was recorded to have highest overall prevalence of 94.84% followed by 86.77% in winter and the lowest being recorded at 76.77% in the summer months (P<0.01) (Table 1and Figure 2).…”
Section: Resultssupporting
confidence: 78%
“…4 to 9 months at 89.86% and more than 9 months at 75.75% (Table 1and Figure 3). Molla and Bandyopadhyay (2016), Poddar et al, (2017) and Jena et al, (2018) found similarly higher and lower rate of prevalence among younger age groups and adult animals, respectively. 0-3months age group was also recorded to have highest prevalence (79.67%) of nematode infection.…”
Section: Resultsmentioning
confidence: 84%
“…These observations were found consistent with previous reports who recorded 65.6%, 63.3%, 63.5% prevalence in Bangladesh, Lahore and Islamabad, respectively (Ijaj et al, 2008;Gadahi et al, 2008;Hasan et al, 2011). However, this finding was comparatively lower than that reported by Poddar et al (2017) who indicated 67.4% overall prevalence in Sherpur District of Bangladesh. Notable that in the study areas, pineapple are prevalent and this pineapple are sometime ingested by ruminants.…”
Section: Resultscontrasting
confidence: 55%